The expected impact of establishing the business incubator at Taif University on supporting and developing small and medium pilot projects in Taif region - Alnqaie, Saud bin Suleiman Hamed (Journal of Economic, Administrative and Legal Sciences, 2018)
The study examined the expected impact of the establishment of the business incubator at Taif University on the support and development of small and medium-sized Pioneer projects in Taif " Exploration Study" The aim of this study to Identify the expected impact of establishing a business incubator at the University of Taif, on supports & development of small and medium-sized Pioneer projects, the researcher was based on the premise that entrepreneurs support the idea of establishing a business incubator at Taif University which it support & help them to make the success of small and medium projects, thus contributing to economic growth. The researcher relied on the descriptive Methodology to collect data. The research community represented the entrepreneurs in the Taif region. The limits of the time research cover the period from 1438-1439 AH and its spatial limits, Taif. The theoretical framework dealt with the relevant "literature", and the questionnaire was used to obtain the preliminary information and analyze it using the statistical package (SPSS). The researcher concluded that the entrepreneurs support the idea of ​​establishing the incubator at Taif University. The most important recommendations made by the researcher "the need to establish a business incubator at the University of Taif to support small and medium Pioneer projects in Taif.